2020
DOI: 10.21203/rs.3.rs-39911/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly predictive regression model of active cases of COVID-19 in a population by screening wastewater viral load

Abstract: The quantification of the SARS-CoV-2 load in wastewater has emerged as a useful method to monitor COVID-19 outbreaks in the community. This approach was implemented in the metropolitan area of A Coruña (NW Spain), where wastewater from the treatment plant of Bens was analyzed to track the epidemic’s dynamic in a population of 369,098 inhabitants. We developed statistical regression models that allowed us to estimate the number of infected people from the viral load detected in the wastewater with a reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…In addition, starting on April 19 th , 24-hour composite wastewater samples were continually analysed until early June, and surveillance will continue at the Bens WWTP until the viral genetic material disappears. The results of this study identified a decrease in COVID-19 incidence and further confirmed that the time course of the quantifiable discovery of SARS-CoV-2 in wastewater was inversely correlated with the number of confirmed COVID-19 cases ( Vallejo et al, 2020 ).…”
Section: Occurrence Of Viruses Worldwide In Wastewatersupporting
confidence: 79%
See 3 more Smart Citations
“…In addition, starting on April 19 th , 24-hour composite wastewater samples were continually analysed until early June, and surveillance will continue at the Bens WWTP until the viral genetic material disappears. The results of this study identified a decrease in COVID-19 incidence and further confirmed that the time course of the quantifiable discovery of SARS-CoV-2 in wastewater was inversely correlated with the number of confirmed COVID-19 cases ( Vallejo et al, 2020 ).…”
Section: Occurrence Of Viruses Worldwide In Wastewatersupporting
confidence: 79%
“…A meta-analysis confirmed that approximately 15% of COVID-19 patients experienced mostly intestinal symptoms and that approximately 10% of patients had intestinal symptoms but not respiratory symptoms ( Ali et al, 2020 ). Correspondingly, SARS-CoV-2 RNA was frequently detected in the faeces of COVID-19 patients who did not experience intestinal symptoms ( Vallejo et al, 2020 , Yeo et al, 2020 ). Several studies reported that approximately 53.9% of patients were positive for faecal viral RNA ( Vallejo et al, 2020 ), and some studies indicated that viruses were excreted in significant amounts in the patients’ stools for an extended period of time ( Chen et al, 2020 ); moreover, in a few cases, the individual was confirmed to be negative based on respiratory samples after a month or more ( Vallejo et al, 2020 , Wölfel et al, 2020 ).…”
Section: Occurrence Of Viruses Worldwide In Wastewatermentioning
confidence: 97%
See 2 more Smart Citations
“…As WBE initiatives rely on the fecally shed viral particles (Collivignarelli et al, 2020; Lodder and de Roda Husman, 2020), an understanding of the predictive ability of this epidemiological metric is necessary for public health units to appropriately action this tool (Hart and Halden, 2020; Hill et al, 2020; Thompson et al, 2020). In particular, studies to date that demonstrate the potential for WBE to identify the onset of community infection prior to clinical testing have largely been applied to identifying first wave of the disease in community (Kaplan et al, 2020; La Rosa et al, 2020; Medema et al, 2020; Nemudryi et al, 2020; Peccia et al, 2020; Sherchan et al, 2020; Vallejo et al, 2020; Wu et al, 2020). Due to limited clinical testing in many countries during the onset of COVID-19 and limited use of wastewater-based SARS-CoV-2 surveillance, it remains unclear whether WBE can have a role in identifying COVID-19 resurgences.…”
Section: Introductionmentioning
confidence: 99%